2018
DOI: 10.3390/pr6080104
|View full text |Cite
|
Sign up to set email alerts
|

Coal Anisotropic Sorption and Permeability: An Experimental Study

Abstract: Knowledge of the bedding plane properties of coal seams is essential for the coalbed gas production because of their great influence on the inner flow characteristics and sorption features of gas and water. In this study, an experimental study on the anisotropic gas adsorption–desorption and permeability of coal is presented. The results show that during the adsorption–desorption process, an increase in the bedding plane angle of the specimen expands the length and area of the contact surface, thereby increasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The derivative effect under the influence of mining can lead to rock bursting and coal and gas outbursts, so the stress evolution characteristics induced by mining have been widely studied. The existing research showed that each component of the 3D crustal stress tensor is always different in different directions, thus playing a major role in influencing the tightness and stability of a mining roadway [3][4][5]. High crustal stress increased the risk of coal and gas outbursts: in the horizontal direction, this and the principal stress intensity are the key factors affecting the risk of an outburst [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The derivative effect under the influence of mining can lead to rock bursting and coal and gas outbursts, so the stress evolution characteristics induced by mining have been widely studied. The existing research showed that each component of the 3D crustal stress tensor is always different in different directions, thus playing a major role in influencing the tightness and stability of a mining roadway [3][4][5]. High crustal stress increased the risk of coal and gas outbursts: in the horizontal direction, this and the principal stress intensity are the key factors affecting the risk of an outburst [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Ten permeability measurements of coal show that the permeability of coal in parallel to the bedding plane in the butt cleat direction is higher than that in perpendicular to the bedding plane. Chen et al , studied the influence of mechanical and permeability properties of coal samples with different intersection angles in parallel and perpendicular to the bedding direction on the process of full stress–strain. Wang et al tested the permeability under the effective stress of 3.5–8.5 MPa, and the results show that the permeability of coal samples decreases exponentially with an increase in effective stress and the dimensionless permeability in parallel to the bedding direction is larger than that in perpendicular to the bedding direction.…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al [11] used the pressure pulse attenuation method to test the permeability of coal and rock before and after low temperature treatment and revealed the influence of liquid nitrogen injection on the permeability of coal seam. Chen et al [12] carried out an experimental study on the adsorption-desorption and permeability of anisotropic gases in coal. It was considered that the permeability of coal sample shows different changes at different stages.…”
Section: Introductionmentioning
confidence: 99%